Development of modern Chinese medicine guided by molecular compatibility theory - Lifeng Luo; Jieru Zhou; Xiaonan Liu; Yanyu Chen; Xiao Du; Lili Gao; Yunting Sun; Shuling Wang (Journal of Advanced Research)
Background: Traditional Chinese Medicine (TCM) has gained global attention, particularly after Professor Youyou Tu was awarded the Nobel Prize for her discovery of artemisinin as a treatment for malaria. However, the theory behind TCM is often perceived as a “black-box” with complex components and an unclear structure and mechanism of action. This had hindered the development of TCM within the framework of modern medicine. Aim of review: The molecular compatibility theory proposed by Professor Tian Xie’s team integrates TCM with Western medicine in clinical practice, and provide a feasible direction for TCM modernization. It is necessary to summarize and popularize this theory. This review aims to systematically introduce this theory to provide some new insight for development of TCM. Key scientific concepts of review: According to the molecular compatibility theory, the desired effects can be achieved by organically combining multiple active molecules from TCM. These TCM molecular compounds have specific ingredients, precise mechanisms, and controllable quality that meet the standards of modern medicine. The molecular compatibility theory has guided the development of antitumor new drug elemene emulsions, and has also revealed extensive compatibility between TCM-derived active molecules and other TCM, Western medicine, or biomaterials. This discovery opens up potential TCM-based treatment options. In conclusion, the molecular compatibility theory holds promise as a strategy for modernizing TCM.